The timing of retirement: New evidence from Swiss female workers - Barbara Hanel; Regina T. Riphahn (Center for Economic Studies and ifo Institute (CESifo), 2012)
We investigate the responsiveness of individual retirement decisions to changes in financial incentives. A reform increased women's normal retirement age (NRA) in two steps from age 62 to age 63 first and then to age 64. At the same time retirement at the previous NRA became possible at a benefit discount. Since the reform affected specific birth cohorts we can identify causal effects. We find strong and robust behavioral effects of changes in financial retirement incentives. A permanent reduction of retirement benefits by 3.4 percent induces a decline in the age-specific annual retirement probability by over 50 percent. The response to changes in financial retirement benefits varies with educational background: those with low education respond most strongly to an increase in the price of leisure.
Keywords: J26; H55; J14; 330; retirement insurance; incentives; social security; labor force exit; natural experiment